Anaylsis framework for Ecosystem of Food, Land, Water Systems (FLWS) actors in Fragile and Conflict-Affected Settings (FCAS) - Dahl, Hauke; Jacobs-Mata, Inga (CGIAR System Organization, 2024)
Analysis framework for Ecosystem of Food, Land, Water Systems (FLWS) actors in Fragile and Conflict-Affected Settings (FCAS) for greater intervention efficiency.